Outcome of Febrile Neutropenia in Children with Cancer: Experience from a Tertiary Health Care Center (KYAMC Journal, 2023)
Background: Febrile neutropenia (FN) is a serious event in children with cancer; associated with various complications and mentionable adverse outcome.Objective: To identify the outcome of febrile neutropenia in children with cancer.Materials and methods: This prospective observational study was conducted from October 2017 to November 2018 in the Department of Pediatric Hematology and Oncology, BSMMU. Children (age